Test and measurements [1999 technology analysis and forecast]. - Masi, C.G.
This article presents a test and measurements technology analysis and forecast for 1999. The subject covered include network instruments, virtual testers, measurement automation, data security and PC-based next-generation instruments
Keywords: AD 1999.; Data security; Measurement automation; Measurements technology; Network instruments; Next-generation instruments; Personal computers; Technology analysis; Technology forecast; Test technology; Virtual testers